Familial Lymphoproliferative Malignancies and Tandem Duplication of NF1 Gene - Gustavo Fernandes; Mirela Souto; Frederico Costa; Edite Oliveira; Bernardo Garicochea (Case Reports in Oncological Medicine)
Background. Neurofibromatosis type 1 is a genetic disorder caused by loss-of-function mutations in a tumor suppressor gene (NF1) which codifies the protein neurofibromin. The frequent genetic alterations that modify neurofibromin function are deletions and insertions. Duplications are rare and phenotype in patients bearing duplication of NF1 gene is thought to be restricted to developmental abnormalities, with no reference to cancer susceptibility in these patients. We evaluated a patient who presented with few clinical signs of neurofibromatosis type 1 and a conspicuous personal and familiar history of different types of cancer, especially lymphoproliferative malignancies. The coding region of the NF-1 gene was analyzed by real-time polymerase chain reaction and direct sequencing. Multiplex ligation-dependent probe amplification was performed to detect the number of mutant copies. The NF1 gene analysis showed the following alterations: mosaic duplication of NF1, TRAF4, and MYO1D. Fluorescence in situ hybridization using probes (RP5-1002G3 and RP5-92689) flanking NF1 gene in 17q11.2 and CEP17 for 17q11.11.1 was performed. There were three signals (RP5-1002G3conRP5-92689) in the interphases analyzed and two signals (RP5-1002G3conRP5-92689) in 93% of cells. These findings show a tandem duplication of 17q11.2. Conclusion. The case suggests the possibility that NF1 gene duplication may be associated with a phenotype characterized by lymphoproliferative disorders.